Financial Literacy and Retirement Planning in the Age of Digital Behavior and Socioeconomic Transformation - Mittal, Gourav (Journal of Social Commerce, 2025)
Financial literacy and retirement planning are critical aspects of personal finance that play a vital role in individuals' financial well-being and long-term security. This paper presents a bibliometric analysis of research articles in the Scopus database focusing on financial literacy and retirement planning. The study aims to explore the most popular authors, publications, and keywords in the literature from an academic perspective. A comprehensive bibliomatrix approach and Biblioshiny, an R-based program was employed to gather and analyze data from scholarly articles published from 2007 to 2022. The findings provide valuable insights into the research landscape of financial literacy and retirement planning and shed light on potential avenues for future research in this field. The keywords "retirement" and "female" were the most frequently used, demonstrating the importance of retirement preparation for women. For researchers in the field of retirement planning, this study offers knowledge that will help them continue to explore these issues.